What Tourism SMEs Should Fix First to Recover Using Principal Component Analysis - Adya Hermawati; Abimanyu Tuwuh Sembhodo; Aviv Yuniar; Syamsul Bahri; Teguh Setiawan Wibowo (Dinasti Publisher, 2026)
Tourism SMEs in East Java have not recovered despite the sector’s high potential. Many struggle to identify which internal factors most influence performance, especially after the pandemic. This research aims to determine the most critical human resource and marketing variables that drive business performance and offer a practical recovery model. This quantitative exploratory research used principal component analysis to reduce and rank ten performance-related variables. The study targeted tourism SMEs in East Java, covering 11 regions with high tourism activity. Researchers selected 200 SMEs using purposive sampling, with three employees and one owner per business, resulting in 800 respondents. Data collection used a structured questionnaire and Likert scale to assess both importance and current performance of each variable. Fieldwork lasted four months. The analysis revealed that risk-taking culture, work security, compensation, employee participation, brand maintenance, risk tolerance, competitor orientation, strategic place, profitability, economic sustainability and customer satisfaction strongly influence business recovery. It also shows that SME performance improves when businesses focus on the highest-impact drivers rather than treating issues in isolation. This research offers a practical model for SME owners to prioritize internal improvements and guides policymakers to deliver more targeted support. The findings can also inform future research in other regions facing similar recovery challenges